PENGARUH WHISTLEBLOWING SYSTEM, GOOD GOVERNMENT GOVERNANCE DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN KECURANGAN DALAM PENGELOLAAN DANA DESA - Ni Luh Gede Kusuma Dewi; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2022)
In preventing fraud, the management of village funds requires supervision, appropriate strategies and firm policies so as to minimize the occurrence of fraud. This study aims to determine the effect of the Whistle-Blowing System, Good Government Governance, and the Effectiveness of Internal Controls on the prevention of fraud in the management of village funds. The population in this study were all employees of the Village Government Office in North Denpasar district. The samples in this study were 72 people who were determined by purposive sampling technique and tested using multiple linear regression analysis techniques. The result of this study, Whistleblowing system has a positive and significant, Good Government Governance has a positive and significant, The effectiveness of internal control has a positive and significant effect on fraud prevention.